State of third party logistics providers in China - Tan, Wee Kwan; Yifei, Z.; Zhang, D.; Hilmola, O. (Emerald Group Publishing, 2014)
Purpose-The purpose of this paper is to identify global trends in the third-party logistics (3PL) industry, and with that to find out where the opportunities and challenges lie, what the critical success factors are, and how companies can position themselves well in China. As there is currently very limited knowledge about the 3PL industry in China, this study also intends to shed light in this area. Design/methodology/approach-The study is conducted through focus group interviews with senior executives of leading 3PL companies in China followed by a survey with 70 logistics companies. Findings-The key strengths of the logistics industry in China include numerous factors such as good connectivity and new infrastructure, while its main weaknesses are a shortage of qualified staff and slow adoption of technologies. There are a number of concerns and issues raised, such as lack of qualified staff, oversupply of warehousing space in China, competition from the influx of foreign 3PL companies to China, and regulations on free trade zones, seaports and airports, all of which may have policy implications. Research limitations/implications-As most of the logistics companies in the study are located and dominating in the Eastern and Southern China, it may be useful to conduct similar study in the new emerging western and central regions of China for comparison. Practical implications-Managers and investors will appreciate the challenges and opportunities in logistics services in China and have a better insight into Chinese logistics development. Originality/value-While China has been viewed as a cost effective place for manufacturing, the logistical costs in China are still very high as compared to other developed countries. This research will highlight the key reasons for the high logistical cost in China.